Generalized AMMI Models for Assessing The Endurance of Soybean to Leaf Pest - Alfian Futuhul Hadi; A. A. Mattjik; IM Sumertajaya (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
AMMI(Additive Main Effect Multiplicative Interaction)model for interactions in two-way table provide the major mean for studying stability and adaptability through genotype × environment interaction (GEI), which modeled by full interaction model. Eligibility of AMMI (Additive Main Effect Multiplicative Interaction) model depends on that assumption of normally independent distributed error with a constant variance. In the study of genotypes’ resistance, disease and pest (insect) incidence on a plant for example, the appropriateness of AMMI model is being doubtful. We can handle it by introducing multiplicative terms for interaction in wider class of modeling, Generalized Linear Models. Its called Generalized AMMI model. An algorithm of iterative alternating generalized regression of row and column estimates its parameters. GAMMI log-link model will be applied to the Poisson data distribution. GAMMI log-link models give us good information of the interaction by its log-odd ratio.